Dihydromyricetin Protects Against Gentamicin-Induced Ototoxicity via PGC-1α/SIRT3 Signaling in vitro - Han, Hezhou; Dong, Yaodong; Ma, Xiulan (Frontiers in Cell and Developmental Biology, 2020)
Aminoglycoside-induced ototoxicity can have a major impact on patient quality of life and social development problems. Oxidative stress affects normal physiologic functions and has been implicated in aminoglycoside-induced inner ear injury. Excessive accumulation of reactive oxygen species (ROS) damages DNA, lipids, and proteins in cells and induces their apoptosis. Dihydromyricetin (DHM) is a natural flavonol with a wide range of health benefits including anti-inflammatory, antitumor, and antioxidant effects; however, its effects and mechanism of action in auditory hair cells are not well understood. The present study investigated the antioxidant mechanism and anti-ototoxic potential of DHM using House Ear Institute-Organ of Corti (HEI-OC)1 auditory cells and cochlear explant cultures prepared from Kunming mice. We used gentamicin to establish aminoglycoside-induced ototoxicity models. Histological and physiological analyses were carried out to determine DHM’s pharmacological effects on gentamicin-induced ototoxicity. Results showed DHM contributes to protecting cells from apoptotic cell death by inhibiting ROS accumulation. Western blotting and quantitative RT-PCR analyses revealed that DHM exerted its otoprotective effects by up-regulating levels of peroxisome proliferator activated receptor γ-coactivator (PGC)-1α and Sirtuin (SIRT)3. And the role of PGC-1α and SIRT3 in the protective effects of DHM was evaluated by pharmacologic inhibition of these factors using SR-18292 and 3-(1H-1,2,3-triazol-4-yl) pyridine, respectively, which indicated DHM’s protective effect was dependent on activation of the PGC-1α/SIRT3 signaling. Our study is the first report to identify DHM as a potential otoprotective drug and provides a basis for the prevention and treatment of hearing loss caused by aminoglycoside antibiotic-induced oxidative damage to auditory hair cells.lls.